Low‐temperature behaviour of K2Sc[Si2O6]F: determination of the lock‐in phase and its relationships with fresnoite‐ and melilite‐type compounds. Issue 5 (20th September 2017) - Hejny, C.; Bindi, L.
Abstract : The commensurate lock‐in phase of K2 Sc[Si2 O6 ]F has been solved and refined from X‐ray single‐crystal diffraction data collected at 25 K. The low‐temperature structure is characterized by octagonal clusters closely resembling those observed in the incommensurate structure of fresnoite‐ and melilite‐type compounds. Abstract : K2 Sc[Si2 O6 ]F exhibits, at room temperature, a (3 + 2)‐dimensional incommensurately modulated structure [ a = 8.9878 (1), c = 8.2694 (2) Å, V = 668.01 (2) Å 3 ; superspace group P 42 / mnm (α, α, 0)000 s (−α, α, 0)0000] with modulation wavevectorsq 1 = 0.2982 (4)(a * +b *) andq 2 = 0.2982 (4)(−a * +b *). Its low‐temperature behaviour has been studied by single‐crystal X‐ray diffraction. Down to 45 K, the irrational component α of the modulation wavevectors is quite constant varying from 0.2982 (4) (RT), through 0.2955 (8) (120 K), 0.297 (1) (90 K), 0.298 (1) (75 K), to 0.299 (1) (45 K). At 25 K it approaches the commensurate value of one‐third [ i.e. 0.332 (3)]: thus indicating that the incommensurate–commensurate phase transition takes place between 45 K and 25 K. The commensurate lock‐in phase of K2 Sc[Si2 O6 ]F has been solved and refined with a 3 × 3 × 1 supercell compared with the tetragonal incommensurately modulated structure stable at room temperature. This corresponds to a 3 × 1 × 3 supercell in the pseudo‐orthorhombic monoclinic setting of the low‐temperature structure, space group P 2/ m, with lattice parameters a = 26.786 (3), b = 8.245 (2) c = 26.824 (3) Å, β = 90.00 (1)°. The structure is a mixed tetrahedral–octahedral framework composed of chains of [ScO4 F2 ] octahedra that are interconnected by [Si4 O12 ] rings with K atoms in fourfold to ninefold coordination. Distorted [ScO4 F2 ] octahedra are connected to distorted Si tetrahedra to form octagonal arrangements closely resembling those observed in the incommensurate structure of fresnoite‐ and melilite‐type compounds.